Advertising during the COVID-19 pandemic: Trends and theoretical developments - Usama Najam; Raza Ali; Umar Burki (Administrative Sciences, 2023)
This study examines how the COVID-19 pandemic affected the trends and theoretical development of advertising research. By using appropriate keywords, this research selected 210 articles from the Web of Science database. We applied bibliometric analysis techniques and employed the VOS viewer to present visualizations. Our findings provide valuable insights into how the COVID-19 pandemic altered advertisers and researchers' perspectives on advertisement content and message strategies. We also explore the application of diversified theoretical lenses to our research on advertisements during the pandemic.
Keywords: 350; advertisement; advertising; COVID-19; media; message strategy; theories